2009
DOI: 10.1021/jp808296c
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Activation of CO2and Possible Corrosion Pathways on the Low-Index Iron Surface Fe(100)

Abstract: Spin-polarized density functional theory (DFT) calculations and periodic slab models were used to study the reactive pathways leading to corrosion products on the low-index (100) surface of iron. We determined the binding energies of CO 2 and the barrier to decomposition of adsorbed CO 2 to O + CO, as well as to the formation of adsorbed CO 3 2and H 2 CO 3 on the Fe(100) surface. The barriers of these pathways were determined with nudged elastic band (NEB) calculations. Short trajectories with DFT-based dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 49 publications
(45 reference statements)
8
54
0
Order By: Relevance
“…The adsorption of both CO and O at the hollow sites released an adsorption energy of -179.9 kJmol -1 , whereas for the co-adsorption of oxygen at the bridge site with CO at the hollow site, an adsorption energy of -143.7 kJmol -1 was released. Our results are consistent with those of Glezakov et al, who reported a co-adsorption energy of -126.0 kJmol -1 for CO and O at the hollow sites using the projected augmented wave pseudopotentials 28 . On the nickel-deposited Fe(100) surface (Figure 6a), the CO moves from the most table hollow site to the bridge site.…”
Section: Co2 Dissociation On Bare and Ni-deposited Fe Surfacessupporting
confidence: 93%
See 4 more Smart Citations
“…The adsorption of both CO and O at the hollow sites released an adsorption energy of -179.9 kJmol -1 , whereas for the co-adsorption of oxygen at the bridge site with CO at the hollow site, an adsorption energy of -143.7 kJmol -1 was released. Our results are consistent with those of Glezakov et al, who reported a co-adsorption energy of -126.0 kJmol -1 for CO and O at the hollow sites using the projected augmented wave pseudopotentials 28 . On the nickel-deposited Fe(100) surface (Figure 6a), the CO moves from the most table hollow site to the bridge site.…”
Section: Co2 Dissociation On Bare and Ni-deposited Fe Surfacessupporting
confidence: 93%
“…For the Fe (100) surface calculations, a p(3 x 3) super-cell was employed for the CO2 adsorption and dissociation reactions, similar to earlier calculations 28,29 . 28, 29 Glezakou et al 28 also obtained the hollow-C2v structure as the preferred CO2 activated mode on the Fe (100) surface with an adsorption energy of -69.9 kJmol -1 , when they studied CO2 corrosion pathways using spin-polarized DFT and norm-conserving pseudopotentials.…”
Section: Adsorption Sites Modes and Strengths Of Co2 On Bare And Ni-mentioning
confidence: 99%
See 3 more Smart Citations